A Just Destination? Exploring Local Hopes, Fears, and Power Asymmetries in East Greenlandic (Tunu) Tourism Development - Markussen, Ulunnguaq; Ren, Carina (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2023)
This paper examines current actions towards tourism development in East Greenland (Tunu) and the expectations and concerns of locals in Tasiilaq, specifically regarding the possible inclusion of the East Greenlandic hunting culture on the UNESCO World Heritage List. We explore how locals see the potential and impact of the UNESCO recognition on tourism development in the region and its potential effects on local economy, culture, and traditions. Also discussed are the structural challenges faced by the local community as well as their aspirations for sustainable tourism development, unraveling the perception of power asymmetries and injustices between locals and outsiders and between East and West Greenland. The complex and often paradoxical relationship between heritage, cultural identity, and economic growth in tourism is highlighted, pointing to how general challenges and barriers in Greenlandic tourism development are further amplified and distorted in East Greenland. This suggests a need for greater tourism justice in developing all and not just parts of Greenland as a destination.